ANALISIS PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DI LINGKUNGAN KECAMATAN PASAR KOTA JAMBI - Rini Yuliani (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2013)
This study is primarily aimed at: (1) explain the effect of leadership and organizational culture on employee performance both simultaneously and partially, and (2) determine which of the two independent variables that has most dominant influence on the employee performance. The results showed that leadership and organizational culture simultaneously influence the employees performance with cooeficent determenation R2is 54.3%. Partially, according to statistical test shows that the independent variables has significant influence on the employee performance. Furthermore, variable that has most dominant influence is leadership. Keywords: Performance Officer; leadership, and organizational culture